Thanks for your ideas: Gratitude and team creativity - Pillay, Nashita; Park, Guihyun; Kim, Ye Kang; Lee, Sujin (Organizational behavior and human decision processes, 2020)
•Gratitude improved idea exchange and development in teams.•Practicing gratitude promoted team creativity.•Teams in the gratitude emotion showed less signs of shallow information processing. Many ideas and products are borne out of collaborative efforts among members of teams and workgroups, and thus finding ways to improve team creativity is of significant interest. Adopting a collective information processing perspective, we argue that gratitude intervention for teams would serve as a powerful facilitator for information elaboration—whereby team members engage in more deliberate and thorough integration of others’ ideas—and, in turn, enhance team creativity. Study 1 found that teams in the gratitude condition increased information elaboration more than those in the neutral condition. Study 2 compared teams in gratitude emotion and teams in positive emotion in general. Teams in the gratitude condition generated highly creative ideas, due to more information elaboration. On the other hand, teams in the positive emotion condition expressed greater enthusiasm and confidence in their ideas and immediately accepted the ideas suggested, which led to an increase in the quantity of ideas. Our findings suggest that gratitude facilitates intellectual exchange in groups, which in turn enhances team creativity. We discuss our findings’ implications for team creativity and potential directions for future research.